Recent progress on perovskite materials in photovoltaic and water splitting applications - Moniruddin, Md; Ilyassov, B; Zhao, X; Smith, E; Serikov, T; Ibrayev, N; Asmatulu, R; Nuraje, N (Elsevier B.V., 2018)
Both inorganic and hybrid (organo-inorganic) perovskite materials are potential candidates as photocatalysts for use in both photovoltaic (PV) and photocatalytic water splitting applications. Currently, research has been focused on specifically designing perovskite materials so they can harness the broad spectrum of the visible light wavelength. Inorganic perovskites such as titanates, tantalates, niobates, and ferrites show great promise as visible light-driven photocatalysts for water splitting, whereas hybrid perovskites such as methylammonium lead halides reveal unique photovoltaic and charge transport properties. The main objective of this article is to examine the progress on some recent research on perovskite nanomaterials for both solar cell and water splitting applications. This mini review paper summarizes some recent developments of organic and inorganic perovskite materials (PMs) and provides useful insights for their future improvement.
Keywords: Perovskite solar cell; Water splitting; Methylammonium lead halides; Photovoltaic; Photocatalyst; Photoelectrochemical cell